Revisiting stock market development and economic growth nexus: The moderating role of foreign capital inflows and exchange rates - Mohammad Enamul Hoque; Noor Azuddin Jakob (Cogent Economics & Finance, 2018)
This study re-examines the stock market development and economic growth nexus. Also, examine the moderating role of foreign capital inflows and exchange rate on the relationship between stock market development and economic growth of Malaysia during 1981-2016. This study applies Granger test, ARDL (with bound testing) approach, and multivariate regression approach to examine extent and direction of the relationships among variabels, empirically. Granger causality test suggests that there are unidirectional effects of stock market development to Malaysian economic growth. Using the bound test for co-integration, this study finds there is a long run association between stock market development and economic growth. However, ARDL model reports that, in the short run and long run, stock market promotes the economic growth of Malaysia which is consistent with Granger causality test. Aditionally, foreign capital inflows and exchange rate has significant positive and negative moderating effects, respectively, on the relationship between stock market development and economic growth. Nevertheless, when both foreign capital inflows and exchange rate interact with each other, there is a joint positive effect on the relationship between stock market development and economic growth. Therefore, Malaysian policy-makers should consider both foreign capital inflows and exchange rate in formulating the economic policy. Moreover, special attention should be given on the external debt, which constitutes a significant proportion of foreign capital inflows, because of its negative impact on economic growth. At the same time, foreign direct investments with flexible exchange rate should be encouraged to foster both stock market and economic growth.
Keywords: C10; F31; F43; F63; F10; 330; economic growth; foreign capital inflows; stock market development; moderation; Malaysia; ARDL approach